A Patient with Eosinophilic Esophagitis and Herpes Simplex Esophagitis: A Case Report and Literature Review. (25th May 2021) - Marella, Hemnishil K.; Kothadia, Jiten P.; Saleem, Nasir; Ali, Bilal; Abdel-Aziz, Yousef; Mupparaju, Vamsee; Oza, Twisha; Azouz, Abdallah; Howden, Colin W.
Abstract : Acute herpes simplex esophagitis (HSE) is common in immunocompromised patients. Eosinophilic esophagitis (EoE) is characterized by immune-mediated eosinophil-predominant esophageal inflammation. We report a patient with human immunodeficiency virus infection who presented with dysphagia and odynophagia and was found to have HSE and EoE. The combination of these two relatively rare conditions suggests possible predisposition.